Environment Matters at the World Bank : Annual Review 2001 - World Bank (2013)
Johannesburg 2002 must be about people, planet, and prosperity; by Mohammed Valli Moosa. Making sustainable commitments - an environment strategy for the World Bank; by Kristalina I. Georgieva. The World Bank's environment strategy consultations; by Judith Moore. From strategy preparation to implementation; by Magda Lovei. Focusing on poverty and environmental links; by Kirk Hamilton, and Jan Bojo. Protecting the global commons; by Todd Johnson. The safeguard policies at the core of the environment strategy; by Jean Roger Mercier. Regional reviews; by Agi Kiss, Giovanna Dore, Holt, Jane, Teresa Serra, Maria Sarraf, and Carter Brandon. IFC - building a sustainable development roadmap - IFC's strategy to ensure environmental and social sustainability; by Shawn Miller. News updates. The Bank's environment portfolio; by Anjali Acharya, and Alethea Mariel T. Abuyuan. Environment by the numbers; by Stefano Pagiola, and Kirk Hamilton.